Curriculum analytics of an Open Distance Learning (ODL) Programme: A data-driven perspective - Mashile, E. O.; Fynn, A.; Matoane, M. (South African Journal of Higher Education, 2023)
Student support, which is an integral part of a learning programme, is most effective when it is integrated into the design of the curricula, rather than when it forms stand-alone interventions. Identifying those areas that require attention from a student support perspective is often based on the perspectives of the institution and teaching staff involved, rather than on how Students concerned interact with the programme. In this article, we draw on the research fields of curriculum analytics to identify areas of curriculum improvement for an ODL programme using student data. The results of the study indicate the important role that is played by curriculum analytics in designing student support interventions, and in restructuring elements of the curriculum structure to support student success. Such is done by ascertaining what constitutes the learned curriculum versus the planned curriculum, the Temporal Distance between Courses, and any bottlenecks within the programme that might hamper progression. The results, further, underscore the need for an effective execution strategy to be aligned with the principles that guided the development of the curriculum concerned.